RESPONSIBILITIES AND CHALLENGES FACED BY WIDOW WOMEN: A SOCIOLWORK STUDY - Barot, Trusha; Parmar, Christina (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of this research is to offer a complete knowledge of the difficulties those widows all over the world experience, as well as the conditions that prevail in families that are headed by women. The raising of awareness about the difficulties that widow’s face in today’s society is the secondary goal of this initiative. Among the scholarly publications that investigate the issue of widows in India from a feminist perspective, there is a conspicuous lack of such publications. This study emphasises the necessity of doing an investigation into the challenges that these women face, as well as the necessity of radically altering our perceptions concerning these issues. In the event that a woman suffers the loss of her spouse, she goes through the process of becoming a widow. The term "widowhood" refers to the psychological state that arises after the death of one spouse. Compared to other types of losses, the death of a husband has a more profound effect on a woman’s life than any other kind of loss. There is still a small portion of the population, specifically widows, whose circumstances have not improved at all, despite the fact that the majority of Indians have experienced a tremendous improvement in their level of living. It is a source of communal shame that our culture treats widows in the manner that it does. As a result of the passing of her husband, a woman’s life goes through a significant transition, which requires her to conform to new social conventions. The primary objective of releasing this essay is to provide a thorough picture of the challenges that the widow encountered. These challenges include the financial and psychological costs that were brought about as a result of the practice’s reliance on particular rituals that the widow was unable to participate in. Despite the fact that there are numerous programmes in India that are designed to provide assistance to widows, the situation of widows continues to be extremely precarious. The efforts that the government is making to alleviate the financial difficulties that widows are experiencing are a step in the right direction; nonetheless, these efforts are not satisfactory enough to meet the needs that are essential. An economically impoverished widow who is also suffering from mental depression, so creating a situation that is favourable to both parties involved. She does not receive adequate support from both society and her family. Despite the fact that widows are legally married, there is a reluctance to face the fact that they are ostracised in society and treated with disrespect from others. Despite the fact that there are a great number of programmes in the country that are designed to aid widows, society does not address the challenges that they face. Thus this paper analyzes the challenges and responsibilities faced by widow women in India.